MODEL OF CONTEXTUAL-BASED ACADEMIC WRITING LEARNING MODULE - Afif Rofii; Fathiaty Murtadho; Aceng Rahmat (English Review: Journal of English Education, 2018)
This research and development aims to develop a contextual-based learning module for academic writing course to develop the students’ writing skill. It adopts Borg Gall’s model modified from Jolly and Bolitho’s model of development steps. The development steps include: assessing the teaching materials currently implemented, designing and developing the module, judging module feasibility by experts, and testing module effectiveness. It applies mixed method approach to describe textual data qualitatively and analyze numerical data using t-test. The data were obtained from need analysis through document analysis, interview, observation, survey, and experiment. The analysis found that the lecturers and students need appropriate, practical and effective teaching materials that meet their needs. Therefore, the module of writing teaching material is developed by integrating the seven components of contextual approach in various learning activities. Th epracticality test suggests that the module is very pratical. The feasibility test 82.27 in average confirming that the module is very feasible to develop. The effectiveness test found that it is very effective reflected in the posttest mean score of experimental class (78.10) that is significally different from the control class (69.80). The tests of practicality, feasibility, and effectiveness come into conclusion that the developed module can be implemented in the academic writing class. As suggesstion, the lecturers and researchers are recommended to develop comprehensively teaching materials aligning with the students’ needs.Keywords: model, contextual-based, academic writing, module, research and development